Strategi Media Konsultan Ilmu Komunikasi Dalam Program Edukasi Literasi Digital Masyarakat - Sumiyati Sumiyati; Muhammad Billi Putera Mas Agung (Puslitbang Akademi Relawan TIK Indonesia, 2026)
The exponential development of information technology has created a digital literacy paradox in Indonesia: high internet penetration does not match the digital literacy skills of the population. This puts Indonesia in a vulnerable position against cybercrime, while also highlighting the crucial role of communication consultants as non-government actors in digital literacy. This study uses a systematic literature review (SLR) method with PRISMA protocols to analyze 42 selected articles from the Scopus, Web of Science, Google Scholar, and DOAJ databases (2015–2025). The synthesis findings show that the Critical Analytical approach is the dominant strategy used by communication consultants, proving relevant for both professional groups and youth. Unlike government programs that tend to be one-way, the consultant approach offers longer interaction times and higher levels of active participation. This study contributes to formulating a consultative communication model that integrates the four pillars of digital literacy (CABE) specifically based on audience demographics. As a practical implication, it is suggested that the government start considering involving communication consultants structurally to complement mass digital literacy programs so they can be more personal and participatory.